Wacana Kesetaraan Gender: Pemikiran Islam Kontemporer tentang Gerakan Feminisme Islam - Andik Wahyun Muqoyyidin (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2013)
Gender is one of discourses called contemporary discourse calls for the attention of many parties, the youth, among movement activists, academics and students, legislative and government, and the theologian. The purpose of this discourse is to close a social injustice based on gender differences. Furthermore, it seeks to achieve equality between men and women in the social aspects. And so far, of the discourse on gender at least can be categorized into four performance, i.e., as a movement, as a discourse of development, those social issues into religious issues, and as an approach in the study of religion. This paper discusses about the perspectives of gender equality as understood by the muslim feminists. In general, it can be mentioned that the purpose of the struggle of feminism is equality, dignity, and freedom of women in choosing and managing life and her body, both inside and outside the household.